Religious Moderation Education: An Interpreation - Pathur Rahman; John Supriyanto; Muhamad Takrip (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
The fact of the dynamics of the views of different religious communities towards the verses of the Koran shows conflict. Moderation education is very important to ask about in social life, especially in the academic world which can be carried out concretely with certain approaches based on values or exemplary technology based where data is compilation in cyberspace and can be used in all areas of life. The qualitative method that the researcher did observed activities in detail related to moderation education through the verses of interpretation in Penakita and analyzed them qualitatively with interview or documentation observation techniques to then analyze the data obtained, the data collected was presented related. The study of Majlis ta`lim at Pena Kita Indralaya Islamic boarding school provides stories of friends, tabi`in and scholars, by developing the concept of religious moderation education through the study of verses of interpretation to teach the congregation a moderate, inclusive and respectful attitude in understanding and implementing religious teachings such as justice, peace, tolerance, and interfaith harmony.